Combination Ability of Melon Powdery Mildew Resistance Varieties and Donor Lines on Yields - Rafikjon Abdunabievich Khakimov (Central Asian Journal of Medical and Natural Science, 2023)
As a result of evaluation of the combinational value of varieties and lines-donors of resistance to powdery mildew of melon, varieties and lines with high combinational ability for yield were identified. Varieties Galaba, Oltin tepa and line L-4 are recommended for breeding as donors of high productivity.